Listen to the emerging markets of Southeast Asia : - Letta, Corrado G. M. (John Wiley & Sons, 1996)
This book introduce Machine derived contents note: Mapping An Investment Strategy. The Global Economy and Transculturalism. The Rationale for a Co-operative Framework. Investing in Southeast Asia: "Risk" or "Opportunity"? Managing Cross-Cultural Communication. A Comparison of European and Asian Corporate Cultures. Negotiating in a Cross-cultural Context. Creating Europe Inc. Learning From the Past. Putting the House of Europe Inc. in Order.